Intraosseous lipoma of the calcaneus: A case report and review of the literature - Cardeña-Mamani, Rakel (2020)
Introduction: Intraosseous lipomas are primary bone tumors described as rare or infrequent that may occur in different ways depending on the degree of evolution, which makes it difficult to be diagnosed when confused with other lesions such as cysts or bone infarctions. Objective: to report the case as a rare pathology and to review the literature. Case Report: The case of a 29-year-old male diagnosed at the Almanzor Aguinaga Asenjo National Hospital –EsSalud – Chiclayo – Peru with an intraosseous lipoma located in the calcaneus is presented, according to the evidence obtained in the imaging studies; subsequently treated by curettage and bone grafting. Together the histopathological study was carried out that supports the diagnosis made. Conclusion: The intraosseous lipoma is a rare benign tumor, however, in the calcaneus bone it is where it occurs most, they are asymptomatic, the diagnosis is incidental on the radiograph as a lytic lesion, with central calcification, which according to the clinic can be treated surgically.